2012
DOI: 10.1007/s11999-011-2100-y
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Technique: Aperture Fixation in PCL Reconstruction: Applying Biomechanics to Surgery

Abstract: Level IV, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…For this reason, we did not pool (meta-analyze) our data. In addition, heterogeneity among studies may have been attributable to differences in other factors that could affect clinical outcome after PCL reconstruction, including the use of a wide variety of autografts and allografts as graft sources, and variability in the use of fixation devices, which have been associated with differences in residual laxity in other studies [4,6]. Finally, not every included study rated every patient based on Tegner and Lysholm scores or the degree of posterior translation by stress radiographs and posterior drawer tests; the missing data may have affected the direction or robustness of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, we did not pool (meta-analyze) our data. In addition, heterogeneity among studies may have been attributable to differences in other factors that could affect clinical outcome after PCL reconstruction, including the use of a wide variety of autografts and allografts as graft sources, and variability in the use of fixation devices, which have been associated with differences in residual laxity in other studies [4,6]. Finally, not every included study rated every patient based on Tegner and Lysholm scores or the degree of posterior translation by stress radiographs and posterior drawer tests; the missing data may have affected the direction or robustness of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…3 A more recent concept in PCL tunnel fixation is aperture fixation. [32][33][34][35] As previously discussed, the killer turn can lead to graft failure and thinning and increased graft length in transtibial techniques. 22,23 Cadaveric studies showed that inlay techniques may eliminate these unwanted effects.…”
Section: Graft Fixationmentioning
confidence: 95%
“…33 The clinical results of aperture fixation have been promising but consist of case series with small numbers. 34,35 Hermans et al 34 reconstructed the anterolateral bundle in 25 patients with PCL instability and pain using BPB autograft, hamstrings autograft, or Achilles allograft using interference screw fixation at the tunnel aperture. They reported good functional outcomes and a mean anteroposterior laxity difference of 2.1 mm between knees measured by KT-1000 (MEDmetric, San Diego, California) at 6-to 12-year follow-up.…”
Section: Graft Fixationmentioning
confidence: 99%
See 2 more Smart Citations